Association of Intrapartum Risk Factors and Infant Clinical Indicators with Culture Confirmed Early Onset Neonatal Sepsis in a Secondary Care Rural Hospital in India. (27th August 2020) - Gandra, Sumanth; Ranga, Shravan K; Hendrixson, D Taylor; Nayakanti, Raghuprakash R; Newland, Jason G; Alvarez-Uria, Gerardo; Jinka, Dasaratha R
Abstract: Objective: The aim of this study is to determine the association of intrapartum risk factors and infant clinical indicators using the National Institute for Health and Care Excellence (NICE) criteria with culture-positive early-onset neonatal sepsis (EONS) from a rural secondary healthcare facility where intrapartum prophylactic antibiotics are routinely administered to high-risk mothers. Methods: A single-center prospective observational study was conducted between July 2017 and September 2018. All intramural neonates with at least one NICE criteria at less than 72 h of life, were included. Univariate logistic regression and multivariable logistic backward elimination analyses were conducted to investigate individual risk factors and predictive models for culture proven EONS. Results: Of 236 newborns who were at risk for EONS by NICE criteria, 32 (13.8%) had positive blood cultures. Klebsiella species ( n  = 13, 39.4%) and Acinetobacter species ( n  = 11, 33.3%) were the most common isolated bacteria. In univariate analysis, the number of infant clinical indicators were associated with culture positive EONS (OR 1.36; 95% CI 1.01–1.81), but not the number of intrapartum risk factors (OR 0.76; 95% CI 0.4–1.29). The multivariate logistic regression with backward elimination procedure suggested that a model including absolute neutrophil count [adjusted OR (aOR) 0.81; 95% CI 0.72–0.92], C-reactive protein (aOR 1.24; 95% CI 1.08–1.43) and the number of clinical indicators (aOR 1.29; 95% CI 0.93–1.80) could be useful to predict culture positive EONS in our setting. Conclusion: In this maternal and neonatal cohort, infant clinical indicators rather than intrapartum risk factors were associated with culture confirmed EONS.